...Em busca da realidade... : a experiência da etnicidade dos Eleotérios (Catu/RN) - Silva, Cláudia Maria Moreira da (2007)
The south region of the Rio Grande do Norte has been historically recognized as a place of old indian villages. Inhabitants of the edges of the Catu River, border between the cities of Canguaretama and Goianinha, the Eleotérios in the threshold of 21st century had passed to be seen and self recognized as "remaining indians" of the RN. Their ethnic mobilizations, when becoming public had placed to the intellectual and political fields an old question to be reflected on: the asseverations concerning the "indian disappearing" in the State. This item brings with it other implications. Accessed by a para-oficial indigenism, the Eleotérios had started to establish political relations with the Potiguara indians of the Baía da Traição/PB and the Indian Movement, feeling stimulated to produce and to reproduce forms of social differentiation. In this context, this research is worried about elucidating the process of construction of the ethnicity among the Eleotérios, percepted from the social relations and politics kept with the amplest society, into a particular historical situation involving sugar cane fields owners, proprietaries, militants, researchers, ambiental agencies. The effects of these political and social relations had been extended, making Eleotérios appear to the society as susceptible social actors to the specific policies for the aboriginal populations